4 - Restructuration et évolution de l'emploi dans le secteur public et parapublic en Côte-d'Ivoire: by Kouadio Benie Marcel - Marcel, Kouadio Benie (Africa Development, 1992)
Faced with both internal and external deficits , Cote-ď Ivoire has embarked upon a restructuration programme of its public and para-statal sector ; The restructuration option is theoretically warranted by the public deficit-external deficit nexus and the very weak performance of public enterprises . To ensure the productive efficiency of state structures and an optimal allocation of resources , measures such as liquidation, privatization and rehabilitation of public enterprises have been carried out. Privatization entailed three different modalities each of which is faced with objective limitations associated with internal bottlenecks. Of these, the major one is the absence of "shumpeterian entrepreneurs". In the process of industrialization , is it possible to do away with the public sector? Presently these reforms have resulted in shrinking employment whose magnitude varies according to the nature of the public enterprises and branches concerned. The deterioration in the employment condition has given rise to such new phenomena as unemployed graduates and extended duration of unemployment.